Economic development dimension of intellectual property as investment in international investment law - Stepanov, Ivan (The Journal of World Intellectual Property, 2020)
Intellectual property (IP) and foreign direct investment (FDI) are seen as important contributors to economic development. However, once given a closer look, a complex economic landscape emerges. Although, both IP and FDI can be beneficial to the economic development of a country their presence does not automatically guarantee it. From a legal perspective, the treaties governing the two international legal regimes, international IP law and international investment law (IIL), reflect the positive developmental aspirations ascribed to IP and FDI. Nevertheless, once these international treaties are put to the test in international adjudication, economic development becomes a contested notion. In particular, investor-state dispute settlement (ISDS) tribunals are often confronted with economic development as a legal concept and the way they treat it can vastly differ. By relying on the Salini test in ISDS cases dealing with IP, the Tribunals had the chance to address the developmental dimension of IP as FDI. Philip Morris v. Uruguay and Bridgestone v. Panama give a detailed outlook on the different outcomes such considerations might result in. Focusing on those cases this article will argue that economic development deserves a place in the realm of IP and IIL.
CRIS-Team Scopus Importer:2020-10-23
Keywords: economic development; foreign direct investment; ISDS; key topics; organizations and agreements; TRIPS

Introducing a property right over data in the EU: the data producer’s right–an evaluation - Stepanov, Ivan (International Review of Law, Computers and Technology, 2019)
The article discusses the nature and justification for the introduction of the data producer’s right. The European Commission in its efforts to boost the European data economy is contemplating the introduction of an IPR over data. Firstly, the article surveys whether the current EU legal framework grants property rights over data and how the established IPRs like copyright or the database protection treat data as the object of property. Secondly, drawing upon property theory the article determines whether the data producer’s right can be regarded as a property right at all. Thirdly, the data producer’s right is assessed in light of some legal and economic justifications for the introduction of property rights. Considering that the Commission proposed the introduction of the right on the grounds of economic policy, the analysis will endeavor to shed some light on whether the current proposal might achieve the stated goals.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Data; EU; property

Investor-State Dispute Settlement and Data: Implications for Data Policy and Regulation - Stepanov, Ivan (GRUR International, 2020)
CRIS-Team Scopus Importer:2024-12-16

Protecting or investing in history? Italian historical trade marks and expropriation under international investment law - Stepanov, Ivan; Valente, Luca (Journal of Intellectual Property Law and Practice, 2020)
CRIS-Team WoS Importer:2020-06-16